A druggable secretory protein maturase of Toxoplasma essential for invasion and egress - Sunil Kumar Dogga; Budhaditya Mukherjee; Damien Jacot; Tobias Kockmann; Luca Molino; Pierre-Mehdi Hammoudi; Ruben C Hartkoorn; Adrian B Hehl; Dominique Soldati-Favre (eLife, 2017)
Micronemes and rhoptries are specialized secretory organelles that deploy their contents at the apical tip of apicomplexan parasites in a regulated manner. The secretory proteins participate in motility, invasion, and egress and are subjected to proteolytic maturation prior to organellar storage and discharge. Here we establish that Toxoplasma gondii aspartyl protease 3 (ASP3) resides in the endosomal-like compartment and is crucially associated to rhoptry discharge during invasion and to host cell plasma membrane lysis during egress. A comparison of the N-terminome, by terminal amine isotopic labelling of substrates between wild type and ASP3 depleted parasites identified microneme and rhoptry proteins as repertoire of ASP3 substrates. The role of ASP3 as a maturase for previously described and newly identified secretory proteins is confirmed in vivo and in vitro. An antimalarial compound based on a hydroxyethylamine scaffold interrupts the lytic cycle of T. gondii at submicromolar concentration by targeting ASP3.